The Effect of Characteristics of Individuals, Competence, and Work Environment on Lecturer Performance in Management Study Programs at University X - R. , Achmad Drajat Aji (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the influence of individual characteristics, competencies, and work environment on the performance of lecturers. The type of research method used is an explanatory survey. The sampling technique uses saturated samples because all populations are used as samples of 96. The number of questionnaires that can be processed is 90 respondents from 96 questionnaires distributed. Analysis of statistical data used is the validity, reliability, classical assumption test, correlation coefficient, coefficient of determination, multiple regression analysis, and hypothesis testing with ANOVA. The results of the data processing influence of individual characteristics, competencies, and work environment on the performance of the lecturers of the Management Study Program at University X showed a correlation coefficient of 0.588, which means that individual characteristics, competencies, and work environment had a fairly strong relationship with lecturer performance significantly. The coefficient of determination is obtained at 0.346, which means that the contribution of individual characteristics, competencies, and work environment to the lecturer’s performance is 34.6%; the remaining 65.4% is influenced by other variables not examined in this study. Partial testing showed that there was a significant effect between individual characteristics, competencies, and work environment with the performance of lecturers, partially with the direction of a positive relationship.